The riddle that never was - Bylton Enid; Ludlow, Patricia (, England Award publications, Worksop, 2009)
The Riddle That Never Was" by Enid Blyton features two young friends, Nick and Katie, who invent a mystery for Katie's uncle, Bob, a private investigator, to solve during his visit.